2018
DOI: 10.1161/circresaha.117.312482
|View full text |Cite
|
Sign up to set email alerts
|

Network Analysis to Risk Stratify Patients With Exercise Intolerance

Abstract: Network analyses were used to identify novel exercise groups and develop a point-of-care risk calculator. These data expand the range of useful clinical variables beyond pVo that predict hospitalization in patients with exercise intolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 34 publications
1
39
0
Order By: Relevance
“…Instead, investigators have demonstrated that abnormal cardiopulmonary measures assessed in combination, based on dichotomous or multi-level thresholds, increases the prognostic value of CPX compared to one marker alone 34 . This concept has since been expanded by implementing sophisticated analytic methods such as network analysis [35][36][37] and machine learning 38 , which apply algorithms to complex data to identify clusters of biomarkers that are highly predictive of an outcome of interest. Most recently, the application of machine learning to commonly available health data in electronic medical records as well as exercise test outcomes…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Instead, investigators have demonstrated that abnormal cardiopulmonary measures assessed in combination, based on dichotomous or multi-level thresholds, increases the prognostic value of CPX compared to one marker alone 34 . This concept has since been expanded by implementing sophisticated analytic methods such as network analysis [35][36][37] and machine learning 38 , which apply algorithms to complex data to identify clusters of biomarkers that are highly predictive of an outcome of interest. Most recently, the application of machine learning to commonly available health data in electronic medical records as well as exercise test outcomes…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…This patient shows both precapillary and postcapillary PH with increased Treatment was directed to both COPD and HFpEF in this patient. This strategy may be useful in phenotyping complex patients from a personalized medicine perspective 2,57 and has been adopted by the Pulmonary Vascular Phenomics Program (PVDOMICS). 1…”
Section: Discussionmentioning
confidence: 99%
“…In this clinical study, Dr. Maron collected and used invasive cardiopulmonary testing data to construct a correlation network. 1 From the exercise network, a subnetwork was developed that included peak volume of oxygen consumption and nine other variables.…”
Section: Session 1: Systems/network Medicine In Clinical Practicementioning
confidence: 99%